Evaluating educational reforms : Scandinavian perspectives - Haug, Peder, 1947-; Schwandt, Thomas A. (Evaluation and society., 2003)
A Scandinavian perspective on evaluating educational reforms. The essays include: The Research Council of Norway Evaluating Reform 97; Models of Evaluation; and What's Being Done in the Name of Evaluation? Experiences Drawn from the Recent Evaluation of Schooling Reforms in Switzerland.